2002
DOI: 10.1002/1099-0690(200206)2002:12<1877::aid-ejoc1877>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Additions to Nitroalkenes

Abstract: The asymmetric conjugate addition of various carbon and heteroatom nucleophiles to nitroalkenes as a tool for the construction of highly functionalized synthetic building blocks is presented. Diastereoselective, substrate-controlled 1,4-additions are also included. Besides auxiliary controlled asymmetric Michael additions, external asymmetric versions employing enantiopure additives, addition-elimination processes with enantiopure leaving groups, and catalytic asym-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
293
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 863 publications
(301 citation statements)
references
References 54 publications
(60 reference statements)
1
293
0
2
Order By: Relevance
“…Racemic products were obtained from the corresponding substrates catalyzed by DABCO at room temperature. 1 H and 13 C NMR spectra were performed on a Brucker-300 MHz spectrometer for products dissolved by CDCl 3 or DMSO-d 6 with tetramethylsilane (TMS) as an internal standard. Optical rotations were measured on a Perkin-Elmer 241 Polarimeter.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Racemic products were obtained from the corresponding substrates catalyzed by DABCO at room temperature. 1 H and 13 C NMR spectra were performed on a Brucker-300 MHz spectrometer for products dissolved by CDCl 3 or DMSO-d 6 with tetramethylsilane (TMS) as an internal standard. Optical rotations were measured on a Perkin-Elmer 241 Polarimeter.…”
Section: Generalmentioning
confidence: 99%
“…It maybe concluded that the causes for this are attributed to the following three factors: (i) the Michael addition reaction belongs to one of the most important C-C bond-forming reactions; 4 (ii) the favorable double-hydrogen-bonding interactions between thiourea moieties and the nitro-group of nitroalkene substrates contribute to promoting the reactivity and selectivity; and (iii) the nitroalkene substrate is more attractive, since the nitro moiety can be easily transformed into a range of different functionalities(a range of functionalities), 5 which lead to important building blocks and products. 6 It is well known that with the asymmetric Michael reaction version, various carbon nucleophiles have been employed in this reaction; however, the use of anthrone as a nucleophile in the analogous transformation is extremely rare. Moreover, a perusal of the literature indicates that only a few examples of organocatalyzed asymmetric reactions of anthrone have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada, Wiechert, and Hajos in 1969, 1971, and 1974) and one of the reactions studied first in 2001 was the Michael addition of ketones to nitrostyrene (List, Barbas, Enders 8 ), a type of reaction dear to the Enders group. 9 While other organocatalysts, such as chiral carbenes, squaramides, and Brønsted acids, were also used by Dieter in previous and subsequent investigations, the most prominent catalysts employed in his recent publications are proline-derived pyrrolidines, especially those of the HayashiJørgensen-type (S)-or (R)-2-[Arl 2 (R 3 SiO)C]-pyrrolidines. 10 It turned out that whole sequences of reactions could be achieved by the same or two different chiral organocatalysts, which would, for instance, activate an enal moiety by iminium-ion formation and an aldehyde group by enamine formation in the same reaction mixture, forming enantiopure products with up to six, sometimes all adjacent stereogenic centers in densely functionalized products; "collaborations" of organocatalysts and organometallic catalysts for performing reaction sequences are also possible.…”
Section: Editorialmentioning
confidence: 99%
“…[1][2][3][4][5] They react as dienophiles, heterodienes, 1,3-dipoles and, above all, as Michael acceptors. [6][7][8] Conjugated nitroalkenes are also distinguished by their biological properties. [9][10][11] Among various biological properties, the anticancer activity of nitroalkenes and their novel MBH adducts with other activated alkenes has highlighted the enormous potential of nitroalkene derivatives as bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%